2021
DOI: 10.1007/s10869-021-09760-5
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Distinct Motives on Promotive and Prohibitive Voice: The Differential Moderating Role of Perceived Voice Level

Abstract: Drawing upon the citizenship motives framework and voice research, this study theorizes that both organizational concern (OC) and impression management (IM) motives are key predictors of employee promotive and prohibitive voice. This study further explores the moderating effect of perceived voice level in the work context on the relationships between motives and voice. The results of 140 pairings of supervisor-subordinate dyads indicate that both OC and IM motives are determinants of promotive and prohibitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…For others, the reluctance to voice was related to impression management motives, whereby employees were concerned that by raising challenging voice to management, they would be looked upon less favourably. This perspective contrasts with the notion that employees will be encouraged to voice due to impression management motives, which has been found as a positive predictor of voice in other voice studies (Zhou, Mao, Liu, & Ning, 2021) and which has also been identified as a means to enhance guanxi i.e., to improve human relationships (Xue, Song, & Tang, 2015). Therefore, rather than seeing voice as a means to improve their relationship with their leader, it was instead seen as jeopardising that relationship.…”
Section: Stifling Of Vertical Voice Due To Leadership Behaviors and N...mentioning
confidence: 85%
“…For others, the reluctance to voice was related to impression management motives, whereby employees were concerned that by raising challenging voice to management, they would be looked upon less favourably. This perspective contrasts with the notion that employees will be encouraged to voice due to impression management motives, which has been found as a positive predictor of voice in other voice studies (Zhou, Mao, Liu, & Ning, 2021) and which has also been identified as a means to enhance guanxi i.e., to improve human relationships (Xue, Song, & Tang, 2015). Therefore, rather than seeing voice as a means to improve their relationship with their leader, it was instead seen as jeopardising that relationship.…”
Section: Stifling Of Vertical Voice Due To Leadership Behaviors and N...mentioning
confidence: 85%
“…Employees with status aspirations at work want to be recognised by others, given the socialrelational setting (Bolino et al, 2008). They may participate to demonstrate their knowledge, talents and capacities while also supporting their communal inclinations (McClean et al, 2018;Weiss and Morrison, 2019;Zhou et al, 2022). Drawing on voice from the OB domain, underpinned at the individual level, we explicate the nature of voice as individual employee behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…They may participate to demonstrate their knowledge, talents and capacities while also supporting their communal inclinations (McClean et al. , 2018; Weiss and Morrison, 2019; Zhou et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%